Anti‐dumping Shock and the Productivity Response of Chinese Industries. Issue 2 (March 2017) - Li, Chunding
Abstract: This paper provides a comprehensive analysis of the productivity effects of antidumping (AD) measures on Chinese industries. Industry‐year panel data and generalized method of moments estimators are used in the empirical analysis. Productivity indicators are calculated using data envelope analysis. The empirical results show that China's industrial total factor productivity has improved under the pressure of AD measures taken by developed countries, and the mechanism inspires technological progress but hurts technological efficiency. Developing countries' AD measures have no significant productivity effects on China's targeted industries, except for slightly positive effects on technological efficiency. These results indicate that China should pay more attention to technological innovation and take different counter‐measures for different cases of AD measures.